Beate Perrey (ed.), The Cambridge Companion to Schumann (2007) - Murphy, Michael (Journal of the Society for Musicology in Ireland, 2008)
A review of Beate Perrey (ed.), The Cambridge Companion to Schumann (Cambridge: Cambridge University Press, 2007), ISBN 978-0-521-78341-5 (hardback, £50/$90); ISBN 978-0-521-78950-9 (paperback, £19.99/$29.99), xx + 302pp.